Pengaruh Sistem Pembayaran Non Tunai (M-Banking) terhadap Tingkat Pertumbuhan Ekonomi Indonesia - Lala Atika Sari; Ario Khasbiyal Ghofur Pranoto; Desti Yuni Aresta (Peneliti.net, 2023)
This journal was created to analyze whether there is an effect of electronic money transactions, per capita income levels, and inflation on economic growth in Indonesia. The development system in the financial sector has transformed from cash payments to cashless payments. Initially, it was only limited to bank transfers through tellers. Then it developed through Automated Teller Machines (ATMs). Furthermore, with the increasing mobility of customers/community, banking devices are required to create products that have higher mobility, creating M-Banking (Mobile Banking), E-Banking (Electronic/Internet Banking), SMS Banking, and so on. This research is a quantitative research, the data is processed using Multiple Regression Analysis. The results of the study show that partially per capita income and inflation do not have a significant effect on economic growth but Electronic Money Transactions have a significant effect on economic growth. Simultaneously Per Capita Income, Inflation Rate, and Electronic Money Transactions have no significant effect simultaneously on the Economic Growth variable.